Procedure for assessing hardware safety integrity in legacy systems. (March 2016) - Kim, Gi Young; Yoo, Ki Hoon; Ko, Byung Gak; Jang, Joong Soon
Abstract: Functional safety is related to the safety functions of a safety-related system that uses electrical/electronic/programmable (E/E/PE) devices such as sensors, logic solvers, and final elements. A legacy system is a safety-related system which offers safety functions but which was not designed to comply with the IEC 61508 standard. This paper presents a procedure for assessing the hardware safety integrity of a legacy system so as to confirm its functional safety. The procedure defines the systematic relationship between the safety function and hardware system using a function-structure map (FSM) and assesses the hardware safety integrity centered on the safety function. The proposed procedure is applied to a boiler control system of a fossil-fuel power plant. Highlights: This research presents a procedure for assessing the hardware safety integrity of a legacy system. A function-structure map is used to respond effectively to the safety functions of the related hardware components and to prevent an error that an SIL evaluation is performed for safety-related systems. The proposed assessment procedure is applied to a boiler control system of a fossil-fuel power plant. The hardware SIL of each safety function is determined to be SIL3 in the boiler control system.